115k views
0 votes
40 points need NOW Simplify the expression.

40 points need NOW Simplify the expression.-example-1
User Mumbasa
by
5.4k points

1 Answer

4 votes

Answer:


7xy^(2) \sqrt[3]{2xy}

Explanation:


\sqrt[3]{686x^(4) y^(7)}


686 = 343 * 2


x^(4) = x^(3) * x


y^(7) = y^(3) * y^(3) * y


\sqrt[3]{343} =7


\sqrt[3]{x^(3)} = x


\sqrt[3]{y^(3)* y^(3)} =
y^(2)

so you're left with 2, x, and y inside the cube root, and 7, x, and y^2 outside


7xy^(2) \sqrt[3]{2xy}

User Shyim
by
5.4k points